Automatic detection of oblique shocks and simple waves in schlieren images of two-dimensional supersonic steady flows. (15th January 2021) - Cammi, G.; Spinelli, A.; Cozzi, F.; Guardone, A.
Highlights: Automatic detection of flow structure within schlieren images of supersonic flows. Accurate Mach number measurements in moderately supersonic flows. Accurate measurement of position and slope of simple waves and oblique shocks. Quantitative application of schlieren technique in non-ideal compressible flows. Experimental characterization of highly non-ideal supersonic flows. Abstract: This paper presents a technique to automatically detect flow structures recorded in schlieren images of supersonic flows. The method provides position and local slope of the detected lines. Salient flow structures considered are shock waves, expansion fans and Mach waves. If the local flow direction is known, the technique provides local Mach number measurement. Moreover, the peculiarities of schlieren technique make the algorithm suitable for Mach measurements in flows where direct velocity measurements are challenged by difficult insemination and for which calibrated aerodynamic pressure probes are not available. The technique is applied to two test cases. In the first case study, the local Mach number is measured at the axis of a supersonic nozzle operated with siloxane vapor MDM. In the second test case, supersonic flow of MDM was analyzed around a diamond shaped airfoil providing the Mach number upstream/downstream oblique shocks/expansion fans and the slope of oblique shocks/fan edges.